Eco-Theological Management and Its Implications for Student Character Development at Al Bahjah Islamic Boarding School - Mochamad Dicky Yudhantaka; Ria Yulia Gloria; Iis Arifudin (MASI Mandiri Edukasi, 2026)
This study addresses the problem of strengthening student character in Islamic boarding schools through value-based educational management. Specifically, it examines how eco-theological management, grounded in tawhid (Islamic monotheism), can be implemented to support holistic character development. The objective of this study is to analyze the implementation of eco-theological management and its implications for student character development at Al Bahjah Islamic Boarding School. This research employs a qualitative case study approach. Data were collected through field observations and semi-structured in-depth interviews involving students, alumni, and parents. The data were analyzed using a descriptive-analytical technique, including data reduction, data display, and conclusion drawing, with triangulation to ensure data validity. The results show that eco-theological management, implemented through the integration of diniyah, tahfidz, and general curricula, contributes significantly to the development of students’ discipline, moral character, independence, and academic competence. Despite limitations in the general curriculum time allocation, continuous evaluation and improvement efforts help maintain educational quality. This study concludes that eco-theological management is an effective and adaptive model for strengthening student character in Islamic educational institutions.